Pellicle formation, microbial succession and lactic acid utilisation during the aerobic deteriorating process of Sichuan pickle. (10th November 2017) - Rao, Yu; Qian, Yang; She, Xiao; Yang, Jiantao; He, Penghui; Jiang, Yunlu; Wang, Meng; Xiang, Wenliang
Abstract: The pellicles formation, microbial changes and lactic acid utilisation during the aerobic deterioration of Sichuan pickle were discussed in this study. By plate counting, chemical detection and HPLC analysis, the aerobic deterioration of Sichuan pickle was featured by microbial growth, pellicle formation, lactic acid decrease and pH elevation. Bacteria dominated in pellicles and the pellicles present morphological change from smooth to wrinkly along with the aerobic deteriorating process. Nine species of bacteria were identified and responsible for the pellicle formation. Combined with Lactobacillus plantarum, eight pellicle‐forming bacteria were the dominant lactic acid consuming organisms in deteriorating Sichuan pickle. Especially under the harsh acid condition of the early deteriorating period, Lb. plantarum, pellicle‐forming bacteria Bacillus amyloliquefaciens, B. subtilis and Citrobacter freundii participated in the pellicles, utilised lactic acid and increased the brine pH effectively. Sequence analysis of 16S rDNA libraries suggested that the resulting pH of 4.8–5.0 initiated the growth of more undesirable organisms, and the pellicle bacterial diversity changed greatly compared with that in the early deteriorating period. The study indicated the important role of pellicles in the initiation of Sichuan pickle's aerobic deterioration and enhanced our ability to understand and potentially control the aerobic deterioration. Abstract : Bacterial floras of pellicles and lactate metabolism in deteriorated Sichuan pickle.